Differences in haul-out pattern in two nursing ringed seal Phoca hispida pups - Christian Lydersen; Morten Skrede Ryg; Mike O. Hammill (Fauna Norvegica, 1993)
This paper describes activity of two nursing ringed seal Phoca hispida pups from Svalbard based on 35 days of continuous recordings from VHF-transmitters glued to the fur of the pups. While still whitecoated the pups spent respectively 10.4% and 63.7% of the recorded time in the water, and were captured or observed at respectively 6 and 7 different breathing holes. The fact that the pups spend much time in the water while still nursing will result in skilled divers at an extremely early age. This, and the high number of breathing holes used by the individual pups, are considered to be adaptations to avoid surface predators.